Women Literacy and Empowerment in India with Reference to Non-Formal Education Model: Exploring the Linkage between Literacy and Women's Empowerment in Rural Areas of Ghana (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Much as knowledge is rationally perceived as power with ability to construct identity, and facilitate social interaction, most women in rural areas in Ghana are unable to read or write in a local language as they missed out on schooling for socio-cultural and structural reasons. Yet, literacy is discounted as an element of personal transformations well as a skill to possibly and cogently bridge the gender-parity gap in education through empowerment projects. The reason being non-formal education programmes which engender acquisition of literacy skills is disparaged as an alternative form of learning in education planning at the detriment of marginalized populations and women in particular. But how can one read the world without the word (Freire Macedo, 1987)?This study primarily identifies the linkage between literacy and women‘s empowerment interrogates the prognosis between literacy and personal transformation and examines the methods employed by Non Formal Education Division to systematize learning to achieve this goal in Ghana. It is an empirical qualitative multi-sited research conducted in four rural locations in Accra tocritically investigate how non-formal education is represented in social development. The study‘s analytical framework is set within a feminist methodology and grounded theory, and draws on transformative learning Mezirow (2000) and empowerment Stromquist (1995) as conceptual frameworks to explore the epistemology and subjective change respectively.